Sportifs, scouts et nationalistes : itinéraire de deux jeunes Vietnamiens (1940-1945) - Brice Fossard (Moussons, 2018)
During the Second World War sport activities and the scout movement in Indochina were managed by the French colonial administration to control the local youth and prevent the rise of nationalism. But in spite of this policy, many young Vietnamese people joined the Vietminh in 1945. By analysing the cases of two Vietnamese teenegers, this article aims to explain how these cultural activities may have played an active role in building their political commitment against France.